Impact of Situational Analysis on Implementation of Educational Innovations in Kenya: The Case of Competency Based Curriculum (CBC) - Wanjara, Amos Otieno; Ogembo, Paul Okeyo (Universitas Pendidikan Ganesha, 2024)
Educational innovation is inevitable in every society. A shift from 8:4:4 to 2:6:3:3:3 (CBC) system of education is ongoing and the new curriculum is taking a centre stage. Situational analysis is a prerequisite for an effective implementation of a new curriculum. However, gaps have been exhibited that are impediments to its effective implementation. The Purpose of this paper was to assess the impact of situational analysis on implementation of CBC. The objectives were to establish the extent: to which curriculum needs assessment were done towards CBC, to which necessary interventions have been taken to address the findings of the situational analysis and to find out the effects of curriculum needs assessment on implementation of CBC. This study reviewed relevant empirical literatures whose meta- analysis was guided by the work of Ferrer (1998). The study established that situational analysis was done towards dispensation of the CBC curriculum but some gaps remained that needed to be addressed before its roll out and continuous support where necessary. This study would necessarily illuminate on policy issues concerning curriculum theory and practice in Kenya.